2023
DOI: 10.3389/fimmu.2022.1025933
|View full text |Cite
|
Sign up to set email alerts
|

Ninety-six–hour starved peripheral blood mononuclear cell supernatant inhibited LA7 breast cancer stem cells induced tumor via reduction in angiogenesis and alternations in Gch1 and Spr expressions

Abstract: IntroductionThe microenvironment of solid tumors such as breast cancer is heterogeneous and complex, containing different types of cell, namely, cancer stem cells and immune cells. We previously reported the immunoregulatory behavior of the human immune cell in a solid tumor microenvironment-like culture under serum starvation stress for 96 h. Here, we examined the effect of this culture-derived solution on breast cancer development in rats.MethodNinety-six–hour starved PBMCs supernatant (96 h-SPS) was collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…We showed the role of anti HSP60 immunity in T1D and T2D as well as in atherosclerosis in our previous studies [ [56] , [57] , [58] , [59] , 59 ]. Moreover, in a rat model of LA7 cancer stem cells induced tumor, we recently showed that the 96h –SPS, induced a severe type of inflammation which was manifested as vast necrotic tumoral tissues [ 29 ]. In the present study in our in silico analysis, we found SLE and RA as top subjects in predicted functions list of PBMCs – and fibroblastic proteome respectively, and T1 D at borderline positivity for the latter proteome.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We showed the role of anti HSP60 immunity in T1D and T2D as well as in atherosclerosis in our previous studies [ [56] , [57] , [58] , [59] , 59 ]. Moreover, in a rat model of LA7 cancer stem cells induced tumor, we recently showed that the 96h –SPS, induced a severe type of inflammation which was manifested as vast necrotic tumoral tissues [ 29 ]. In the present study in our in silico analysis, we found SLE and RA as top subjects in predicted functions list of PBMCs – and fibroblastic proteome respectively, and T1 D at borderline positivity for the latter proteome.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we used the identical protein data set which has been published previously [ 29 ]. This data set was prepared from mass spectrometry analysis of human PBMCs culture supernatant which is briefly described in the next section.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations